Effect of a model consultation informed by guidelines on recorded quality of care of osteoarthritis (MOSAICS): a cluster randomised controlled trial in primary care. Issue 10 (October 2017) - Jordan, K.P.; Edwards, J.J.; Porcheret, M.; Healey, E.L.; Jinks, C.; Bedson, J.; Clarkson, K.; Hay, E.M.; Dziedzic, K.S.
Summary: Objective: To determine the effect of a model osteoarthritis (OA) consultation (MOAC) informed by National Institute for Health and Care Excellence (NICE) recommendations compared with usual care on recorded quality of care of clinical OA in general practice. Design: Two-arm cluster randomised controlled trial. Setting: Eight general practices in Cheshire, Shropshire, or Staffordshire UK. Participants: General practitioners and nurses with patients consulting with clinical OA. Intervention: Following six-month baseline period practices were randomised to intervention ( n = 4) or usual care ( n = 4). Intervention practices delivered MOAC (enhanced initial GP consultation, nurse-led clinic, OA guidebook) to patients aged ≥45 years consulting with clinical OA. An electronic (e-)template for consultations was used in all practices to record OA quality care indicators. Outcomes: Quality of OA care over six months recorded in the medical record. Results: 1851 patients consulted in baseline period (1015 intervention; 836 control); 1960 consulted following randomisation (1118 intervention; 842 control). At baseline wide variations in quality of care were noted. Post-randomisation increases were found for written advice on OA (4–28%), exercise (4–22%) and weight loss (1–15%) in intervention practices but not controls (1–3%). Intervention practices were more likely to refer to physiotherapy (10% vs 2%, odds ratio 5.30; 95% CI 2.11, 13.34), and prescribe paracetamol (22% vs 14%, 1.74; 95% CI 1.27, 2.38). Conclusions: The intervention did not improve all aspects of care but increased core NICE recommendations of written advice on OA, exercise and weight management. There remains a need to reduce variation and uniformly enhance improvement in recorded OA care. Trial registration number: ISRCTN06984617.